A cross-sectional historical study on the changes in self-esteem among Chinese adolescents from 1996 to 2019 - Li, Min; Xu, Qinghong; Han, Xiangwei; Jiang, Yongzhi; Ya, Ru; Li, Jie (Frontiers in Psychology, 2023)
This study aimed to investigate the changes in self-esteem levels among Chinese adolescents from 1996 to 2019. In this cross-sectional historical study, 109 articles using the Rosenberg Self-esteem Scale (SES) were selected from three Chinese and five English databases. The results showed that: (1) The self-esteem level of Chinese adolescents was positively correlated with the period, indicating that the self-esteem of Chinese adolescents was gradually increasing. (2) The increase in self-esteem level of girls was higher than that of boys. (3) The increase in the self-esteem level of only child was higher than that of non-only child. (4) The self-esteem level of rural adolescents increased year by year. However, the self-esteem level of urban adolescents was not significantly correlated with the years. (5) The changes in macro social factors can significantly predict the upward trend of the self-esteem level of Chinese adolescents.